2021
DOI: 10.1002/ams2.651
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of medical emergencies related to dental treatment: a retrospective single‐center study

Abstract: Although uncommon, medical emergencies arise in general dental practice. Inadequate data on their severity and frequency makes targeting medical education for general dental practitioners difficult. This also makes planning for unexpected events challenging for practitioners and makes collaborating with emergency physicians burdensome. We aimed to clarify the incidence and characteristics of a dental outpatient department's medical emergencies.Methods: This single-center, retrospective, observational study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Within this study, the medical emergency frequency rate of 0.037% was considered to be higher compared to other retrospective international studies. 6,[14][15][16] Based on the number of dental visits, Obata et al reported 0.0037% over an 8-year period, Anders et al reported 0.016% over an 8-year period, and Sorenson et al reported 0.0079% over a 7-year period. The most likely reason for a higher occurrence within this study is due to the variances in the inclusion criteria from previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Within this study, the medical emergency frequency rate of 0.037% was considered to be higher compared to other retrospective international studies. 6,[14][15][16] Based on the number of dental visits, Obata et al reported 0.0037% over an 8-year period, Anders et al reported 0.016% over an 8-year period, and Sorenson et al reported 0.0079% over a 7-year period. The most likely reason for a higher occurrence within this study is due to the variances in the inclusion criteria from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies only reported medical emergencies that resulted in a dispatch of a medical team, or when the establishment of an intravenous line was required for the patient. 15,16 Other reasons include varying definitions in what was classified as a medical emergency between the studies as well as the acknowledgment of under-reporting of minor events by other authors into the incident reporting system database. 16 Incidents tend to go unreported or unnoticed if they are being managed without a medical emergency team or assistance by paramedics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations